How early should VATS be performed for retained haemothorax in blunt chest trauma? - Lin, Hsing-Lin; Huang, Wen-Yen; Yang, Chyan; Chou, Shih-Min; Chiang, Hsin-I.; Kuo, Liang-Chi; Lin, Tsung-Ying; Chou, Yi-Pin (Injury, 2014)
Blunt chest injury is not uncommon in trauma patients. Haemothorax and pneumothorax may occur in these patients, and some of them will develop retained pleural collections. Video-assisted thoracoscopic surgery (VATS) has become an appropriate method for treating these complications, but the optimal timing for performing the surgery and its effects on outcome are not clearly understood. In this study, a total of 136 patients who received VATS for the management of retained haemothorax from January 2003 to December 2011 were retrospectively enrolled. All patients had blunt chest injuries and 90% had associated injuries in more than two sites. The time from trauma to operation was recorded and the patients were divided into three groups: 2–3 days (Group 1), 4–6 days (Group 2), and 7 or more days (Group 3). Clinical outcomes such as the length of stay (LOS) at the hospital and intensive care unit (ICU), and duration of ventilator and chest tube use were all recorded and compared between groups. The mean duration from trauma to operation was 5.9 days. All demographic characteristics showed no statistical differences between groups. Compared with other groups, Group 3 had higher rates of positive microbial cultures in pleural collections and sputum, longer duration of chest tube insertion and ventilator use. Lengths of hospital and ICU stay in Groups 1 and 2 showed no statistical difference, but were longer in Group 3. The frequency of repeated VATS was lower in Group 1 but without statistically significant difference. This study indicated that an early VATS intervention would decrease chest infection. It also reduced the duration of ventilator dependency. The clinical outcomes were significantly better for patients receiving VATS within 3 days under intensive care. In this study, we suggested that VATS might be delayed by associated injuries, but should not exceed 6 days after trauma.